Risk of transmission of foot-and-mouth disease by wild animals: infection dynamics in Japanese wild boar following direct inoculation or contact exposure - Katsuhiko Fukai; Rie Kawaguchi; Tatsuya Nishi; Mitsutaka Ikezawa; Manabu Yamada; Kingkarn Boonsuya Seeyo; Kazuki Morioka (Veterinary Research, 2022)
Abstract Understanding of disease dynamics and viral shedding in wild boar and of the potential for disease spreading within wild boar and domestic pig populations is critical for developing effective control and eradication measures for foot-and-mouth disease (FMD). Accordingly, we infected experimentally wild boar and domestic pigs with FMD virus (FMDV) strains O/TAI/315/2016 and A/MOG/2013, and studied their susceptibility and viral transmissibility in both populations. Similar to FMDV-infected pigs, wild boar inoculated with both viruses exhibited vesicular lesions on their feet, snout, tongue and lip, although they did not show lameness. Further, inoculated wild boar were equally capable of transmitting the virus to all of their contact animals. While all contact pigs developed vesicular lesions after contact with inoculated animals, in contrast, no wild boar when exposed to the same infected animals showed obvious clinical signs. These results will be useful for further understanding of the critical roles in occurring and sustaining an FMD outbreak, and will be useful for establishing epidemiological surveillance programs and effective countermeasures for wild boar.